Endocytosis of somatodendritic NCKX2 is regulated by Src family kinase-dependent tyrosine phosphorylation - Lee, Kyu-Hee; Ho, Won-Kyung; Lee, Suk-Ho (Frontiers in Cellular Neuroscience, 2013)
We have previously reported that the surface expression of K+-dependent Na+/Ca2+ exchanger 2 (NCKX2) in the somatodendritic compartment is kept low by constitutive endocytosis, which results in the polarization of surface NCKX2 to the axon. Clathrin-mediated endocytosis is initiated by interaction of the μ subunit of adaptor protein complex 2 (AP-2) with the canonical tyrosine motif (YxxΦ) of a target molecule. We examined whether endocytosis of NCKX2 involves two putative tyrosine motifs (365YGKL and 371YDTM) in the cytoplasmic loop of NCKX2. Coimmunoprecipitation assay revealed that the 365YGKL motif is essential for the interaction with the μ subunit of AP-2 (AP2M1). Consistently, either overexpression of NCKX2-Y365A mutant or knockdown of AP2M1 in cultured hippocampal neurons significantly reduced the internalization of NCKX2 from the somatodendritic surface and thus abolished the axonal polarization of surface NCKX2. Next, we tested whether the interaction between the tyrosine motif and AP2M1 is regulated by phosphorylation of the 365th tyrosine residue (Tyr-365). Tyrosine phosphorylation of heterologously expressed NCKX2-WT, but not NCKX2-Y365A, was increased by carbachol in PC-12 cells. The effect of carbachol was inhibited by PP2, a Src family kinase (SFK) inhibitor. Moreover, PP2 facilitated the endocytosis of NCKX2 in both the somatodendritic and axonal compartments, suggesting that tyrosine phosphorylation of NCKX2 by SFK negatively regulates its endocytosis. Supporting this idea, activation of SFK enhanced the NCKX activity in the proximal dendrites of dentate granule cells. These results suggest that endocytosis of somatodendritic NCKX2 is regulated by SFK-dependent phosphorylation of Tyr-365.